Efektivitas Strategi Pemasaran dalam Membangun Kepercayaan Pengguna Pada BKKBISA - Atika Dwi Mabruroh; Netti Nurlenawati; Dexi Triadinda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In maintaining the growth of a business, efforts are needed to develop effective marketing strategies including digital marketing with the marketing mix method and strategies in increasing user trust. This study aims to determine the effectiveness of marketing strategies in building BKKBISA user trust. The research method used was a qualitative approach, data collection techniques were carried out by interview, observation, and documentation with the director of PT TNR Solution Indonesia, BKKBISA users, and HR. Sinergia (BKKBISA partnership). The results of this study indicate that the marketing strategy carried out by BKKBISA in building user trust is with product strategy, price, place, promotion, people, process, and physical evidence. In addition, stratregies are also used in increasing consumer confidence, such as ability, benevolance, and integrity. From the application of these strategies, it was found that the marketing strategy carried out was effective, this was evidenced by the increase in the number of BKKBISA users from before, namely from 516,861 users in early November 2023 to 546,539 users in December 2023. This increase has a good effect on the development of the company